2003
DOI: 10.1063/1.1557526
|View full text |Cite
|
Sign up to set email alerts
|

The settling velocity of heavy particles in an aqueous near-isotropic turbulence

Abstract: The ensemble-average settling velocity, V s , of heavy tungsten and glass particles with different mean diameters in an aqueous near-isotropic turbulence that was generated by a pair of vertically oscillated grids in a water tank was measured using both particle tracking and particle image velocimetries. Emphasis is placed on the effect of the Stokes number, St, a time ratio of particle response to the Kolmogorov scale of turbulence, to the particle settling rate defined as (V s ϪV t)/ V t where V t is the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 27 publications
13
75
4
Order By: Relevance
“…Numerical modelling has shown that turbulence could enhance the sedimentation (flotation) velocities of heavy (light) particles (Wang and Maxey 1993, Yang and Lei 1998, Bosse et al 2006, De Lillo et al 2008. There are also several laboratory studies that examine how turbulence can modify the vertical velocity of small particles (Aliseda et al 2002, Brucato et al 1998, Ruiz et al 2004, Ross 2006, Schimdt and Seuront 2008, Yang and Shy 2003, Zhou and Cheng 2009. Some studies show a reduction of the sedimentation velocity of synthetic particles in turbulent waters (e.g.…”
Section: Modulation Of Cell Sinking Speedmentioning
confidence: 99%
“…Numerical modelling has shown that turbulence could enhance the sedimentation (flotation) velocities of heavy (light) particles (Wang and Maxey 1993, Yang and Lei 1998, Bosse et al 2006, De Lillo et al 2008. There are also several laboratory studies that examine how turbulence can modify the vertical velocity of small particles (Aliseda et al 2002, Brucato et al 1998, Ruiz et al 2004, Ross 2006, Schimdt and Seuront 2008, Yang and Shy 2003, Zhou and Cheng 2009. Some studies show a reduction of the sedimentation velocity of synthetic particles in turbulent waters (e.g.…”
Section: Modulation Of Cell Sinking Speedmentioning
confidence: 99%
“…Aliseda et al (2002) and Yang & Shy (2005). These studies are closely related, but their focus is on different aspects of two-way coupling (i.e.…”
Section: Earlier Workmentioning
confidence: 99%
“…Because of the low number of particles, it is difficult to determine if preferential concentration effects are absent or if the particle statistics are insufficient. However, one could argue that preferential concentration effects will not be significant owing to the relatively high values of the ratio of the particle terminal velocity and the fluid fluctuations, β = u tv /u (Yang & Shy 2005). This corresponds to a low 'residence time' of the particles in a typical vortical structure.…”
Section: Preferential Concentration Effectsmentioning
confidence: 99%
See 2 more Smart Citations